On the lower bound of vertex connectivity of semiregular cages - Balbuena C.; González-Moreno D.; Lin Y.; Marcote X. (Utilitas Mathematica, 2010)
A semiregular cage is a graph with degree set r, r+1, girth g and the smallest possible order. In this work we prove that semiregular cages with r ≥ 3 and odd girth g ≥ 7 are t-connected with t ≥ ⌊√r +(3/2)2 - 1/2⌋.